2007
DOI: 10.3324/haematol.11034
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-related leukemia and myelodysplasia: susceptibility and incidence

Abstract: Therapy-related myelodysplastic syndrome/acute myeloid leukemia (t-MDS/AML) is an increasingly recognized treatment complication in patients treated with radiotherapy or chemotherapy for previous hematologic malignancies or solid tumors. Distinct clinical entities have been described according to the primary treatment, corresponding to defined genetic lesions. Chromosome 7 and/or 5 losses or deletions are typical of alkylating agent-induced AML, while development of t-AML with balanced translocations involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
2
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 70 publications
3
139
2
11
Order By: Relevance
“…Irrespective of these details, our data suggest the intriguing possibility to kill malignant myeloblast by inhibiting (one of) the upstream kinase(s) that account for constitutive activation of the NF-kB pathway. Although other studies suggested that ATM might be used as a chemo-or radiosensitizing agents (Leone et al, 2007), the result of our work implies that ATM inhibition as such could have a therapeutic effect on high-risk MDS and AML. This hypothesis warrants further preclinical and clinical exploration.…”
Section: Discussioncontrasting
confidence: 58%
“…Irrespective of these details, our data suggest the intriguing possibility to kill malignant myeloblast by inhibiting (one of) the upstream kinase(s) that account for constitutive activation of the NF-kB pathway. Although other studies suggested that ATM might be used as a chemo-or radiosensitizing agents (Leone et al, 2007), the result of our work implies that ATM inhibition as such could have a therapeutic effect on high-risk MDS and AML. This hypothesis warrants further preclinical and clinical exploration.…”
Section: Discussioncontrasting
confidence: 58%
“…13,80 MDS/AML risk after allogeneic HCT is thought to be comparable to that of other cancer survivors who have received particular cytotoxic chemotherapeutic agents and radiotherapy, with such risks often exceeding 10-fold. 81 There is also some evidence that MDS/AML risks may be even higher after autologous HCT because of the substantial cumulative doses received during pre-transplant chemotherapy and radiotherapy, chemotherapy-based stem cell mobilization and HCT conditioning. 62,82,83 …”
Section: Magnitude Of Riskmentioning
confidence: 99%
“…Patients usually developed t-MDS or t-AML with a latency ranging from 22 to 46 months after receiving chemotherapy [3]. Cytogenetic abnormalities such as losses or deletions of chromosome 7 and/or 5 and recurrent balanced translocations involving 11q23 and 21q22 are frequently observed in t-AML and t-MDS, and are regarded as important hallmarks for the diagnosis of these two entities [4]. Our patient demonstrated unusual clinical features.…”
Section: Discussionmentioning
confidence: 66%